2020
DOI: 10.1108/jfc-01-2020-0003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Ponzi schemes and revocation of licences of some financial institutions on financial threat in Ghana

Abstract: Purpose The purpose of this study was to assess the effects of the Ponzi schemes and revocation of licences of some financial institutions in Ghana on financial threat. Design/methodology/approach The study adopted a quantitative research approach. Convenient sampling method was used to select 435 individuals from three regions in Ghana. Standardize questionnaire developed by the researcher was used as the main data collection instrument. The binary logistic regression was used to test the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Therefore, the general perception is that the advent of microfinance will contribute to equal financial service opportunities and eventually reduce poverty. Nonetheless, Ghana's MFI sustainability and poverty reduction ability have received massive criticism over the years [25][26][27]. For example, in 2015, some eight MFIs had their licenses revoked over suspected Ponzi schemes.…”
Section: Hypothesis 3 (H3)mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the general perception is that the advent of microfinance will contribute to equal financial service opportunities and eventually reduce poverty. Nonetheless, Ghana's MFI sustainability and poverty reduction ability have received massive criticism over the years [25][26][27]. For example, in 2015, some eight MFIs had their licenses revoked over suspected Ponzi schemes.…”
Section: Hypothesis 3 (H3)mentioning
confidence: 99%
“…For example, in 2015, some eight MFIs had their licenses revoked over suspected Ponzi schemes. In 2016, an additional 70 MFIs' licenses were revoked for their inability to meet requirements introduced as part of the central bank's measures to sanitize the sector [27].…”
Section: Hypothesis 3 (H3)mentioning
confidence: 99%
“…Given that the microfinance industry is diverse in status comprising both regulated and unregulated MFIs, the finding also confirms Thibaut and Mathias (2014), who argue that capitalization matters in financial institution lending behavior even when regulatory capital requirements are not binding. Financial institutions with lower capitalization could be more risk averse and limit their loan supply in order to fulfill market constraints since the market (including institutional and retail depositors, among others) requires adequate capitalization for the risk the financial institution assumes; the level of capitalization is a good indicator of bank/MFI insolvency, which is one of the reasons for revocation of licenses of some financial institutions in Ghana (Ofori, 2020).…”
Section: Econometric Resultsmentioning
confidence: 99%
“…Building a strong reputation is a paramount concern for Ghanaian banks, particularly in the aftermath of the banking sector crisis, where banks' reputation has been viewed negatively by customers (Ofori, 2023;Osakwe et al, 2020). Yomboi et al's study (2021) revealed that the crisis had significant impacts on customers, leading to the loss of capital, reduced motivation for further savings, difficulties in repaying creditors and a general decline in the ability to cater to customer needs, such as educational plans.…”
Section: Introductionmentioning
confidence: 99%
“…Building a strong reputation is a paramount concern for Ghanaian banks, particularly in the aftermath of the banking sector crisis, where banks' reputation has been viewed negatively by customers (Ofori, 2023; Osakwe et al. , 2020).…”
Section: Introductionmentioning
confidence: 99%